Efeitos da nicotina na sensibilidade ao contraste visual em adultos não fumantes - Fernandes, Thiago Monteiro de Paiva (2021)
The main purpose was to investigate the effects of nicotine on contrast sensitivity in non smokers. This research was conducted into two studies: (1) investigation of achromatic sensitivity (vertical sinusoidal gratings with spatial frequencies ranging from 0.2 to 15.9 cycles per degree; n = 13); and (2) investigation of chromatic discrimination (using the Cambridge Colour Test, CCT; n = 21). Thirty-four participants, aged 18 to 40 years, were randomized and enrolled in different studies (different participants for each one of the controlled clinical trials) involving administration of placebo or nicotine gum (2-mg and 4- mg). Repeated measures multivariate analyses of variance were conducted to analyze the outcomes of each study. Bayesian statistics were also conducted to confirm the findings and to avoid bias. Results indicated that nicotine gum administration resulted in better visual discrimination when compared to the placebo gum (p < .001). More specifically, the 4-mg resulted in better visual sensitivity when compared to the 2-mg (p < .01) and the placebo (p < .001) gums. Blinding was not broken and no significant differences for adverse events were observed. Sociodemographic data were not related to the visual tests. These preliminary results bring the need to support these findings, specially using physiological measures. If proved, it is possible that nicotine, in small doses, can have adjuvant therapeutic and pharmacological actions for those populations with disorder, especially those affecting basic visual functions. This will require controlled research designs and more investigations.